Development Students Worksheet Using Ethnomathematics-based CTL Approach on SLETV Subject Material for Grade X - Mursalina, Ditya; Marhamah, Marhamah; Retta, Allen Marga (Kreano, Jurnal Matematika Kreatif-Inovatif, 2021)
This study aims to produce worksheets using an ethnomatematic based CTL approach on SLETV material that is valid and practical. This type of research and development is R&D. The ADDIE development model consists of: analyze, design, development, implementation, evaluation. However, this research is limited to the implementation stage for individual trials (one to one) and small group trials. The results of this study were obtained from the aspects of validity and practicality. a) the validity aspect is obtained based on 3 validators with assessment aspects based on content, construct, and language with the first validator score of 84.61% in the "valid" category then the second validator is 92.30% with the very valid category and the third validator is 86.53 % with a valid category. b) the practicality aspect is obtained based on 9 student response questionnaires given in the small group trial stage completed with an average score of 83.79% and categorized as "practical".Penelitian ini bertujuan untuk menghasilkan produk LKS Menggunakan Pendekatan CTL berbasis etnomatematika pada materi SLETV yang valid dan praktis. Jenis penelitian dan pengembangan ini adalah R&D. Model pengembangan ADDIE terdiri dari: analyze, design, development, implementation, evaluation.Namun pada penelitian ini dibatasi pada tahap implementasi untuk uji coba perorangan (one to one) dan uji coba kelompok kecil (small group). Hasil penelitian ini di peroleh dari aspek kevalidan dan kepraktisan. a) aspek kevalidan diperoleh berdasarkan 3 validator dengan aspek penilaian berdasarkan isi, konstruk, dan bahasa dengan skor validator pertama yaitu 84,61% dengan kategori Ã¢â‚¬Å“validÃ¢â‚¬Â kemudian validator kedua 92,30% dengan kategori sangat valid dan validator ketiga yaitu 86,53% dengan kategori valid. b) aspek kepraktisan diperoleh berdasarkan 9 angket respon siswa yang diberikan pada tahap uji coba kelompok kecil selesai dengan skor rata-rata 83,79% dan dikategorikan Ã¢â‚¬Å“praktisÃ¢â‚¬Â.